1997
DOI: 10.1016/s0005-2736(96)00222-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NAP-22 and GAP-43 (neuromodulin) as major protein components in a Triton insoluble low density fraction of rat brain

Abstract: NAP-22 is a membrane-localized brain enriched acidic protein having a Ca(2+)-dependent calmodulin binding activity. Further fractionation of the NAP-22 containing membrane showed the localization of NAP-22 in a Triton insoluble fraction of low density. Besides NAP-22, this fraction was found to contain GAP-43 (neuromodulin), trimeric G proteins, and some GPI-anchored proteins such as Thy-1 and N-CAM-120. Presence of some protein tyrosine kinases, such as src and fyn, was also shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…GAP-43 is enriched in DRMs isolated from rat brain (40). To determine whether GAP-43 is present in PC12 cell DRMs, solubilized DRMs were incubated with anti-GAP-43 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GAP-43 is enriched in DRMs isolated from rat brain (40). To determine whether GAP-43 is present in PC12 cell DRMs, solubilized DRMs were incubated with anti-GAP-43 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of TIF from Rat Brain-TIF was prepared as described previously with slight modification (13). All procedures were carried out on ice or at 4°C, unless otherwise mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE, Western blotting using ECL system (Amersham Pharmacia Biotech), and protein determination were performed as described (13). Anti-Thy-1 antibodies were obtained from Cedarlane and Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…The palmitoylation motif of GAP-43 can mediate lipid raft association for protein trafficking to the axonal membrane. Indeed, previous studies have found that GAP-43 is enriched in DIGs from brain homogenates (31) and is transported to axons on vesicles derived from the secretory pathway (32). On the other hand, signals within the body of PSD-95 working together with palmitoylation may mediate its association with dendritic targeting vesicles and its exclusion from rafts.…”
Section: Targeting Of Peripheral Membrane Proteins In Neurons 44987mentioning
confidence: 96%